Special distillation processes - Lei, Zhigang (Elsevier, 2005)
Special distillation processes are required for separation of mixtures close to boiling point or for forming azeotrope mixtures into their pure components. In Special Distillation Processes, the authors focus on latest developments in the field, such as separation methods that may prove useful for solving problems encountered during research. Topics include extraction, membrane and adsorption distillation involving the separation principle, process design and experimental techniques. The relationship between the processes and the techniques are also presented. Comprehensive and easy-to-read, this book provides key information needed to understand the processes and is a valuable reference source for chemical engineers as well as students wishing to branch out in chemical engineering. * The only comprehensive book available on special distillation processes * Contains a thorough introduction to recent developments in the field * A valuable reference for students and engineers in chemical engineering.